Peranan Perempuan dalam Lembaga Eksekutif pada Dinas Perikanan dan Kelautan Kabupaten Timor Tengah Utara - Tri Anggraini; Serliana Tmaneak; Aplonia Pala; Anita Lassa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aims to determine the main duties and functions of the role of women in the Fisheries Service of North Central Timor Regency. The research method used is descriptive qualitative. This type of research is used to describe or analyze the role of women in executive institutions in the Fisheries Service of North Central Timor Regency. Women play an important role in formulating policies in the TTU District Fisheries Service. The role of women as administrators of government affairs has become the duty and responsibility of the department so that those who serve as administrators always support the TTU district community optimally by the vision and mission of the department. The role of women as administrators is very important. Plays an important role in the world of work, especially offices, so that administrative implementation does not deviate from the corridors of the agency. The role of women as supervisors of implementing units is also very important in the world of work because without supervisors the tasks they carry out will not be carried out well. In conclusion, the role of women as administrative implementers plays a very important role in the world of work, especially in offices, so that administrative implementation does not deviate from existing corridors within the agency. Implementing unit coaches are also very important in the world of work because without a coach the tasks carried out will not be carried out well. Keywords: Executive Agency, Role Of Women, TTU fisheries service